Microbiological Evaluation of the Pathogens Isolated From the Endotracheal Aspirate Samples of the Patients Followed in the Intensive Care Units: A One-Year Retrospective Analysis Reply - Sagmak-Tartar, Ayse (Aves, 2018)
[Abstract Not Available]
Yazarın yanıtı